Absence of a Context‐General Behavioural Syndrome in a Solitary Predator. (17th December 2012) - Nyqvist, Marina J.; Gozlan, Rodolphe E.; Cucherousset, Julien; Robert Britton, J.; Wright, J.
Abstract The correlation of seemingly unrelated behaviours into behavioural syndromes has been established in a wide range of species and taxa. However, most studies report on short‐term behavioural correlations without insight into individual consistency or temporal stability of the behavioural syndrome. Here, we examine the individual repeatability of single behaviours, and the presence and temporal stability of a context‐general behavioural syndrome in a solitary piscivorous predator, the pike (Esox lucius). Behavioural measurements on the same individuals were quantified independently through time and across three contexts: activity in the presence of a competitor, exploration of a novel environment and boldness under predation risk. There was no indication of a temporally stable behavioural syndrome, consisting of boldness, activity and exploration, nor were individuals consistent in the separate behaviours, contradicting the general assertion of its taxonomic prevalence. Furthermore, the study did not provide support for size or growth‐dependent behaviour in this size‐dimorphic species in conditions of limited food availability. The study highlights the importance of independent multiple observations of individual behaviour across time or contexts when measuring behavioural repeatability and covariation.